Human-in-the-Loop Moral Decision-Making Frameworks for Situationally Aware Multi-Modal Autonomous Vehicle Networks: An Accessibility-Focused Approach (Journal of Computational Intelligence and Robotics, 2022)
The ethical implications of autonomous decision-making in AVs necessitate the development of robust frameworks that guide the vehicle's actions in unavoidable accident scenarios. These frameworks must consider not only the safety of the vehicle's occupants but also the potential impact on bystanders and the surrounding environment. Utilitarian ethics, which prioritize maximizing overall utility or well-being, often form the basis of such frameworks. However, this approach can be challenged in situations where difficult choices must be made, such as sacrificing the life of one passenger to save multiple pedestrians.For instance, a utilitarian framework might dictate that an AV swerve to hit a single pedestrian rather than collide with a bus full of passengers. While this decision may maximize overall well-being by saving more lives, it raises concerns about the fairness of sacrificing one innocent person to save others. Additionally, utilitarian frameworks can be difficult to implement in practice, as they often rely on complex calculations of the potential consequences of various actions. These calculations can be fraught with uncertainty, particularly in situations with incomplete information or rapidly evolving circumstances.Beyond the limitations of utilitarianism, other ethical frameworks also present challenges when applied to AV decision-making. Deontological ethics, which emphasizes following universal moral rules, can be inflexible in situations where adhering to a rule might lead to a worse outcome. For example, a deontological framework might dictate that an AV should always prioritize the safety of its occupants, regardless of the potential consequences for bystanders. This approach could result in the AV sacrificing the lives of pedestrians even when a swerving maneuver could avoid a collision altogether.Virtue ethics, which focuses on developing good character traits, offers a less rigid framework but can be subjective and difficult to operationalize in the context of machine decision-making. How can we program an AV to embody virtues such as compassion, courage, and justice? These are complex questions that require ongoing philosophical and technological exploration.To address these complexities, this paper proposes a moral decision-making framework for AVs that incorporates principles from various ethical schools of thought. The framework emphasizes the following core considerations:• Safety as the Paramount Principle: The primary objective of the AV's decision-making process should always be to minimize harm to human life. This principle aligns with the core tenets of most ethical frameworks and ensures that the safety of all individuals, including elderly and disabled passengers who may be more vulnerable in an accident, remains the top priority.• Transparency and Explainability: The decision-making process of the AV should be transparent and explainable to users. This can be achieved by developing algorithms that are not only effective but also interpretable, allowing users to understand the reasoning behind the AV's actions. For instance, the AV could provide an explanation of its decision-making process after a near-miss scenario, highlighting the factors it considered and the rationale behind its chosen course of action. This transparency can foster trust and acceptance among users, particularly those with pre-existing anxieties about relying on automated systems.• Respect for Human Values: The framework should incorporate respect for fundamental human values such as fairness, non-discrimination, and the sanctity of human life. This necessitates considering the potential impact of the AV's decisions on all individuals involved, including those with disabilities who may have different needs and vulnerabilities. For example, the framework should avoid prioritizing the survival of younger passengers over elderly passengers in an accident scenario.• Contextual Awareness: The framework should account for the specific context of the situation when making decisions. Factors such as weather conditions, traffic density, and the presence of vulnerable road users (e.g., pedestrians, cyclists, children) should all be factored into the AV's decision-making process. By considering the context, the AV can tailor its actions to minimize harm in a way that is sensitive to the specific circumstances.• Continuous Learning and Improvement: The ethical decision-making framework should be a living document that can evolve and adapt over time. As AV technology advances and real-world data is collected, the framework should be refined to address new ethical challenges and scenarios. This continuous learning process is crucial for maintaining public trust and ensuring the responsible development and deployment of AV technology.Impact on Public Trust and Acceptance:The ethical considerations outlined in this paper have a significant impact on public trust and acceptance of AV technology. By prioritizing safety, transparency, and respect for human values, AV developers can build public confidence in the ability of these vehicles to operate safely and ethically on our roads. This is particularly important for elderly and disabled individuals who may be more apprehensive about using a new transportation system. By ensuring that AVs are programmed to make decisions that align with human ethical intuitions, we can foster a future where AV technology empowers individuals of all abilities to live more independent and fulfilling lives.